2010
DOI: 10.1073/pnas.0912116107
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibitor of growth-4 promotes IκB promoter activation to suppress NF-κB signaling and innate immunity

Abstract: Ing4 is a member of the inhibitor of growth (ING) family of chromatin-modifying proteins. Biochemical experiments indicate that Ing4 is a subunit of the HB01-JADE-hEAF6 histone acetyltransferase complex responsible for most nucleosomal histone H4 acetylation in eukaryotes, and transfection studies suggest that Ing4 may regulate a wide variety of cellular processes, including DNA repair, apoptosis, cell-cycle regulation, metastasis, angiogenesis, and tumor suppression. However, in vivo evidence for a physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 30 publications
6
60
0
Order By: Relevance
“…Global and/or gene-specific histone covalent modifications change accompanied by alterations of enzymes associated with those marks is an epigenetic hallmark that is frequently found in tumor cells, similar alterations have also been found in carcinogen exposed cells [109].…”
Section: Histone Marks and Their Effects On Chromatin Structure In Humentioning
confidence: 99%
“…Global and/or gene-specific histone covalent modifications change accompanied by alterations of enzymes associated with those marks is an epigenetic hallmark that is frequently found in tumor cells, similar alterations have also been found in carcinogen exposed cells [109].…”
Section: Histone Marks and Their Effects On Chromatin Structure In Humentioning
confidence: 99%
“…p37Ing1 in mice regulated Bax levels in a negative way and worked as a prosurvival molecule following DNA damage independent of p53 status, complicating the function of ING1 in mouse and human and in various other circumstances. Moreover, recent experiments have also suggested that there are p53-independent functions for the ING proteins, including regulation of the NF-kB and hypoxia inducible factor (HIF) pathways [49][50][51][52]. ING2 shows a high rate of homology with ING1 about 70% [9,10,30,34,53].…”
Section: Biological Functions Of Ing Family Genesmentioning
confidence: 99%
“…Regulation of NFκB activity by ING4 may be due to a physical interaction between ING4 and p65 (RelA), a subunit of NFκB, that results in decreased activation of the canonical NFκB-responsive promoter in brain tumor cells (30). A previous study showed that ING4 promotes IκB promoter activation to suppress NFκB signaling (35). The present study did not investigate whether ING4 directly interacted with p65 or how ING4 regulates the NFκB signaling pathway to induce the differential expression of NFκB target genes.…”
Section: A B Cmentioning
confidence: 99%